Chitosan, polyethylene oxide/polycaprolactone electrospun core/shell nanofibrous mat containing rosuvastatin as a novel drug delivery system for enhancing human mesenchymal stem cell osteogenesis - Ghasemvand, Fariba; Kabiri, Mahboubeh; Hassan-Zadeh, Vahideh; Simchi, Abdolreza (Frontiers in Molecular Biosciences, 2023)
Due to the potential positive effects of rosuvastatin (RSV) on human mesenchymal stem cells (MSCs) osteogenesis and new bone regeneration, it is crucial to develop a suitable carrier that can effectively control the release profile of RSV. The primary objective of this study was to introduce a novel drug delivery system based on core/shell nanofibrous structures, enabling a sustained release of RSV. To achieve this, coaxial electrospinning was employed to fabricate chitosan (CS)+polyethylene oxide (PEO)/polycaprolactone (PCL) nanofibrous mats, wherein RSV was incorporated within the core of nanofibers. By optimizing the relevant parameters of the electrospinning process, the mats' surface was further modified using plasma treatment. The fibers' shape, structure, and thermal stability were characterized. The wettability, and degradation properties of the fabricated mats were also examined. In vitro studies were conducted to examine the release behavior of RSV. Additionally, the capability of MSCs to survive and differentiate into osteocytes when cultured on nanofibers containing RSV was evaluated. Results demonstrated the successful fabrication of CS+PEO+RSV/PCL core/shell mats with a core diameter of approximately 370 nm and a shell thickness of around 70 nm under optimized conditions. Plasma treatment was found to enhance the wettability and drug-release behavior of the mats. The nanofibrous structure, serving as a carrier for RSV, exhibited increased proliferation of MSCs and enhanced osteogenic differentiation. Therefore, it can be concluded that CS+PEO+RSV/PCL core/shell nanofibrous structure can be utilized as a sustained-release platform for RSV over an extended period, making it a promising candidate for guided bone regeneration.